Moral judgement and cognitive complexity development through an instructional design - Frisancho, Susana (1996)
The objective of this study was to test the efficiency of an educacional program (PECC) in order to improve moral reasoning and cognitive complexity. The sample was 18 tenth-grade students of both genders, aged 15-16 years. Even though there were no structural advances in the moral reasoning leve!, there was an increase of reasoning complexity and in the number of elements that the subjects were able to identify in social dilemma.